The Effect of Different Multiples and Methods of Selecting Comparable Firms on the Multiple Valuation Accuracy - Le, Hoang Thu Van (2020)
Using a sample of 1211 largest US firms in the period 2015 – 2019, I examine the valuation accuracy of different methods of selecting comparable firms using two different frameworks: One approach is based on valuation errors and the other relies on cross-sectional regression analysis. Although there are different methods of choosing peer firms, generally they can be divided into industry membership and industry combined with a firm’s fundamentals. By studying three different multiples, namely price-to-earnings (P/E), price-to-book (P/B) and enterprise-value-to-EBITDA (EV/EBITDA), my study finds that industry membership is the most effective portfolio of peer firms in valuation using P/E and EV/EBITDA. However, P/B multiples obtain the highest accuracy by choosing comparable firms based on both industry and firm’s fundamentals. Therefore, my study adds explanation to the variations of suggested set of comparable firms in previous findings. In addition, I also investigated the effect of adjusting multiples for leverage and forecasted accounting values on valuation performance.